THE CAUTIOUS FACULTY: THEIR AWARENESS AND ATTITUDES TOWARDS INSTITUTIONAL REPOSITORIES - A., Abrizah (Malaysian Journal of Library and Information Science, 2009)
This paper reports on a web-based survey carried out on academics of a research intensive university in Malaysia, investigating their use of open access repositories, advocacy undertaken, and reasons for contribution or non-contribution to Institutional Repositories (IRs). The outcome of this study is to provide an institutional repository (IR) that will preserve and disseminate digital materials created by, or associated with the university. Specifically, the objectives of the study are to investigate (a) the issues in establishing a facility to provide open access to research materials, and (b) the potential of an IR and the requirements of a good digital repository in allowing faculties to contribute resources to the institutional repository. Using a mixture of closed and open questions, the survey explored the faculty’s awareness, experiences and opinions of open access publishing, and the university’s IR. Responses were received from 131 academics from 14 faculties, institutes and centres at the university. Science-based faculty members were overwhelmingly in favour of permitting the deposit of research work. More than 60% of the respondents mentioned allowing the deposit of theses and dissertations. Findings indicated that, as users, the academics wanted to find many more types of material in the repository and as authors, they were willing to deposit. Complete theses, post-prints and conference papers were acceptable to be deposited in the IR. Respondents’ support of open access principle and altruism in making their scholarly work publicly accessible were the most important motivators for the academics depositing their work, closely followed by the prospect of an increase in the accessibility of their work. The greatest deterrents were the ownership of copyrights and plagiarism. Other reasons that might impede self-archiving were the pre-print culture, publishers’ policy, trust of readers and preservation. Findings indicated that faculty who planned to contribute to the IR in the future agreed with of the concept of open access and had a greater altruism in making their work publicly accessible. It was also found that a mandate from an institutional employer or a research funder to self-archive would meet with very little resentment and less resistance from the respondents. Based on the findings of the literature review and the survey, appropriate recommendations were made for the university’s repository.